Перспективи використання водневих енергоперетворюючих систем для утилізації теплових вторинних енергоресурсів високотемпературних теплотехнологічних комплексів - Кошельнік, О.В.; Чорна, Н.А. (Проблемы машиностроения, 2014)
Для утилізації низькотемпературних теплових вторинних енергоресурсів запропоновано схему енергоперетворюючого комплексу для одночасного вироблення теплової та електричної енергії із застосуванням водневої турбоустановки та термосорбційного компресора. Наведено етапи розрахунку основних елементів енерготехнологічного комплексу. Проведено аналіз його роботи в діапазоні температур димових газів на вході в теромосорбційний компресор 523–723 К та визначено основні характеристики водневого контуру енергосилової установки. Отримана електроенергія може бути використана для вироблення водню на технологічні потреби. Для утилизации низкотемпературных тепловых вторичных энергоресурсов предложена схема энергопреобразующего комплекса для одновременного производства тепловой и электрической энергии с применением водородной турбоустановки и термосорбционного компрессора. Представлены этапы расчета основных элементов энерготехнологического комплекса. Проведен анализ его работы в диапазоне температур дымовых газов на входе в теромосорбционный компрессор 523–723 К и определены основные характеристики водородного контура энергосиловой установки. Полученная электроэнергия может быть использована для производства водорода на технологические нужды. The scheme of energy conversion complex for the simultaneous thermal and electric power production with the application of hydrogen turbine unit and thermal sorption compressor for waste recovery of low-temperature secondary thermal power resources has been proposed. A structure and basic design stages of the metal hydride systems for energy technological hydrogen processing have been determined. It allows to calculate system operation and completely to define a complex of structural and operation parameters which characterize its general effectiveness. The technique and calculation algorithm of thermo-sorption interaction metal-hydride - hydrogen is developed for case using the kinetic factor. The analysis of unit operation in a range of flue gas temperatures 523–723 K at the inlet to the thermal sorption compressor has been carried out and the main characteristics of the hydrogen circuit of the power plant have been determined. The obtained electric power can be consumed by electrolyzing plants for hydrogen production for the needs of technological processes.